2000
DOI: 10.2466/pr0.86.2.375-378
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Similarities in Psychological Reactions to Infertility

Abstract: A 74-item especially developed and validated questionnaire for Iranian culture was administered three times to 37 Iranian infertile couples and 10 fertile couples acting as control group, namely, initial consultation, during treatment, and on completion of treatment. In view of parallel data also reported for Western patients interest centered on the results of two out of the five factors measured by the questionnaire, i.e., Psychological Stress and Social Behaviour. Analysis generally showed significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on a national probability sample of women in the USA, King (2003) concludes that the effects of sub-fecundity on general anxiety disorder are not moderated by treatment. Some studies show that the length of treatment is not related to the level of stress (Anderson et al 2003), but several researchers have reported contradictory findings (Chiba et al 1997, Nasseri 2000. One unanswered question is whether changes in distress over time are a response to treatment or whether they are a result of the duration of infertility.…”
Section: Research On the Psychology Of Infertilitymentioning
confidence: 99%
“…Based on a national probability sample of women in the USA, King (2003) concludes that the effects of sub-fecundity on general anxiety disorder are not moderated by treatment. Some studies show that the length of treatment is not related to the level of stress (Anderson et al 2003), but several researchers have reported contradictory findings (Chiba et al 1997, Nasseri 2000. One unanswered question is whether changes in distress over time are a response to treatment or whether they are a result of the duration of infertility.…”
Section: Research On the Psychology Of Infertilitymentioning
confidence: 99%
“…Emotionally, the experience is similar in different cultures. For example, a childless couple in Iran show the same reaction about social behaviour and psychological stress as couples in western countries do (6). As always, the field of reproductive phenomena is surrounded by numerous strong values and attitudes.…”
Section: Introductionmentioning
confidence: 99%